Improving the Quality of Pesantren through Quality Management Santri at the Pesantren Al-Iman Bulus - Abdulloh Hadziq; Umi Kultsum (The Institute of Research and Service Community IPMAFA Pati, 2021)
Improving the quality of Islamic boarding schools (pesantren) is strongly influenced by the quality of students (santri). Therefore, the quality management of santri must be managed properly. The purpose of this study is to determine the quality improvement of pesantren through good quality management of santri at the Pesantren Al-Iman Bulus, Gebang, Purworejo. This type of research is qualitative research with a descriptive approach. Sources of data were obtained from boarding school advisers, asatidz (Islamic teachers) council, and santri through in-depth interviews, observation, and documentation. The data analysis used in this study is an interactive analysis of Miles and Huberman. The results of this study indicate that improving the quality of pesantren is carried out through improving the quality management of santri. Improved management includes placing new students at the levels according to their abilities, improving the process by providing education in the form of learning activities from elementary to Ma'had Aly, increasing results (output) by being equipped with religious abilities and skills so that graduates can compete with graduates from other educational institutions, and increasing benefits (outcomes) by providing socialization and motivation to continue their education to a higher level. In addition, there are innovations to equip graduates so that they can provide benefits for their social life.